Producers versus Profiteers: The Politics of Class in Newfoundland during the First World War - O’Brien, Mike (Acadiensis, 2011)
During the First World War a widespread public impression that merchants were taking advantage of the conflict to extract excessive profits became a major issue in Newfoundland politics, and a cause of widespread public discontent. The Fishermen’s Protective Union and other labour organizations were able to use the profiteering issue as a catalyst for political mobilization, and by 1917 had succeeded in forcing the state to take a greater role in regulating the economy. While their gains turned out to be short-lived, the episode marked a significant moment in the history of collective action by Newfoundland’s labouring classes. Résumé Au cours de la Première Guerre mondiale, l’impression courante parmi le public selon laquelle les marchands tiraient avantage du conflit pour soutirer des profits excessifs devint un enjeu de premier plan dans la vie politique à Terre-Neuve et la cause d’un mécontentement public répandu. Le Fishermen’s Protective Union et d’autres organisations syndicales surent utiliser la question du mercantilisme comme un catalyseur de mobilisation politique et réussirent en 1917 à forcer l’État à accroître son rôle en matière de régulation de l’économie. Bien que leurs gains se soient avérés de courte durée, l’épisode marqua un moment déterminant dans l’histoire de l’action collective des classes ouvrières de Terre-Neuve.